Programa gestão nota 10: implicações para a gestão democrática na rede estadual de educação do Piauí - Araújo, Rafaela de Morais (2023)
This research problematizes the public-private management in education, based on the partnership signed between the Department of Education of the State of Piauí and the Ayrton Senna Institute. Its central objective is to analyze the adherence to the Management Program Note 10 - PGN10 by the referred state, debating the implications of the same for the democratic management and, consequently, for the management of the public school, from 2008 to 2017 – period of its validity in the state. The specific objectives sought: to analyze the relationship established between the public and the private, from the context of the State Reform in Brazil and its reflexes for the use of public-private partnership as a new educational management tool; to analyze the context of creation, the structure, the functioning and the political and ideological foundations of the Ayrton Senna Institute, identifying the school management model in its Management Program Note 10; specify the school management model of the State Public Education Network of Piauí defined in local legislation and regulations. To carry out this study, an investigation of qualitative approach was defined, based on documentary research with bibliographic support. This was accomplished through the use of content categories (Management Model and Mechanisms; Training of Managers; Provision of Director Position) as analysis tools. To achieve the objectives, we analyzed the documents made available by the Ayrton Senna Institute to the partner schools (site materials, manuals, spreadsheets, forms, printed texts), as well as important documents in the configuration of the educational policy of Piauí. Authors such as: Adrião (2001; 2008; 2018), Caetano; Peroni (2022), Luz (2009); Silva (2019) and Paro (2002; 2011; 2015). Regarding the category Management Model and Mechanisms, the data pointed to the impact of the Program on local democratic management, achieved by the private management model. With regard to the category Training of Managers, it was observed the use of the strategy of creation of the leader, as a supposed "protagonist" of civil society, devaluing the role of the school manager in the educational context. With regard to the category Provision of Director Positions, there was a retreat in democratic processes and the advancement and expansion of partnerships with the private sector, intensifying control over public educational management, in the name of the discourse built on "efficiency and management by results" strengthened by the Management Program Note 10. From these results, it was found a greater centralization in the processes of choice for school directors implemented by SEDUC-PI, causing changes in the scope of the management of the state education network, minimizing the autonomy of the school community. Therefore, this Program had a significant impact on the management of education in Piauí, creating obstacles to the promotion of democratic management in its education network.